2007
DOI: 10.1002/bit.21517
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional fibrous PLGA/HAp composite scaffold for BMP‐2 delivery

Abstract: A protein loaded three-dimensional scaffold can be used for protein delivery and bone tissue regeneration. The main objective of this project was to develop recombinant human bone morphogenetic protein-2 (rhBMP-2) loaded poly(D,L-lactide-co-glycolide)/hydroxylapatite (PLGA/HAp) composite fibrous scaffolds through a promising fabrication technique, electrospinning. In vitro release of BMP-2 from these scaffolds, and the attachment ability and viability of marrow derived messenchymal stem cells (MSCs) in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 23 publications
4
128
0
1
Order By: Relevance
“…[131] For instance, a composite nanofiber composed by PLGA and hydroxyapatite (HAp) was developed by electrospinning, for recombinant human bone morphogenetic protein-2 (rhBMP-2) delivery. [132] Authors demonstrated that rhBMP-2 was successfully loaded into the composite nanofibers, being released in a controlled manner (2-8 weeks) without loss of its integrity. [132] Since bone regeneration treatment is difficult and complex to access, this strategy might orientate researchers for new therapeutic solutions.…”
Section: Poly(lactic-co-glycolic) Acid Nanofibersmentioning
confidence: 99%
“…[131] For instance, a composite nanofiber composed by PLGA and hydroxyapatite (HAp) was developed by electrospinning, for recombinant human bone morphogenetic protein-2 (rhBMP-2) delivery. [132] Authors demonstrated that rhBMP-2 was successfully loaded into the composite nanofibers, being released in a controlled manner (2-8 weeks) without loss of its integrity. [132] Since bone regeneration treatment is difficult and complex to access, this strategy might orientate researchers for new therapeutic solutions.…”
Section: Poly(lactic-co-glycolic) Acid Nanofibersmentioning
confidence: 99%
“…Several researchers have utilized this well-characterized copolymer for encapsulation and release of a wide variety of bioactive molecules and drugs including TGF-b, BMPs, IGFs, VEGF, NGF, DNA, vancomycin, gentamysin, cisplatin, and others. [261][262][263][264][265][266][267][268] To successfully fabricate and encapsulate PLGA scaffold with these molecules, a wide variety of creative approaches have been taken such as emulsion freeze-drying, 269 nano and microparticle encapsulation, [270][271][272] double emulsion solvent extraction, 273 electrospinning, [274][275][276] compression molding, 277 and others. As mentioned earlier, a fundamental problem with utilizing growth factors is their characteristic short half life in physiological environments.…”
Section: Common Copolymers In Bone Engineeringmentioning
confidence: 99%
“…One study reported a burst release during the first 5 days, with complete release within 20 days. [36] The release profiles for scaffolds prepared by electrospinning with a co-axial spinneret or from a solution mixed with bioactive molecules are similar to each other: there is an initial burst release followed by a sustained, first order release. [41] The initial burst release can be attributed to the migration of the growth factors during the drying process, which tends to concentrate a certain fraction of the growth factor molecules near the surface of the fibers.…”
Section: Incorporation Of Bioactive Moleculesmentioning
confidence: 99%